(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The first chapter included the introduction and the importance of research in finding a new strategy in learning the skill of chest handling in basketball. It is important to present a kind of modern strategies such as educational models supported by kinetic sentences. The research aimed to prepare educational units in the educational model according to the various kinetic sentences and learn the skill of chest handling Basketball, and knowing the effect of the educational units and the educational model according to the various kinetic sentences in learning the skill of handling the chest with basketball. And to identify which of the two groups of the control and experimental groups developed more according to the approach followed by the experimental group and the impact of the strategy of educational models and motor sentences of the control group. It included the sample, the tools used, pre-tests and post-tests as well as statistical methods. The researcher chose a sample of second-stage students / Al-Salam University College / Department of Physical Education and Sports Sciences, and they were divided into two groups (control - experimental) and they were subjected to the tests that he set for them The researcher then subjected the experimental group to an educational curriculum, after which the researcher conducted the post-tests using the appropriate statistical methods to know the pre- and post-tests.. The third chapter included a presentation of the results reached from the pre- and post-tests that were applied to the research sample, and scientific results were reached, and then Discussing it.. The fourth chapter included the most important conclusions, which is the superiority of the experimental group, to which educational models were applied using various kinetic sentences, over the control group, which applied the curriculum followed by the subject teacher in learning the skill of chest handling with basketball. The researcher recommends emphasizing the use of educational models in the lesson of physical education and sports sciences to learn the skill of handling the chest in basketball. It is better to include exercises that contain a variety of dynamic sentences in practical lessons to learn the skill of handling basketball among students.Keywords (educational models, kinetic sentences, chest handling skill in basketball).extracted search.